Default settings affect children's decisions about whether to be honest - Zhao, Li; Mao, Haiying; Zheng, Jiaxin; Fu, Genyue; Compton, Brian J.; Heyman, Gail D.; Lee, Kang (Cognition, 2023)
Behavioral economics research has revealed that our decision-making can be biased by default settings. That is, all other things being equal, adults tend to choose default options even when the effort involved in choosing other options is minimal. Extensive evidence shows that default settings can systematically influence adult decisions in a wide variety of domains (e.g., pension choices, organ donation), but little is known about their developmental origin. Of interest in the present research is whether default settings can influence young children's decisions about whether to be honest. We investigated this question in two studies of 5- and 6-year-old Chinese children (total N = 120; 60 girls; Mage = 5.81, SDage = 0.14). Each study used a specially designed device that allowed children to play a guessing game in either a Cheating Default condition in which they would cheat by doing nothing or in an Honesty Default condition in which they would be honest by doing nothing. In each condition, they had the option of taking a trivially easy action to override the default (pushing a button in Study 1 or moving a screen in Study 2). In both studies, children decided to cheat significantly more often in the Cheating Default condition than in the Honesty Default condition. Additionally, overall cheating rates were significantly higher in Study 2 than in Study 1 (55% vs. 25%), which suggests that even though the default setting effect generalized across different actions, the specific action in question can also affect the cheating rate. Taken together, these results indicate that default setting effects that have been observed in adults have origins in childhood, and they point toward new ways to use nudges to promote positive social development and moral decision-making.
Gesehen am 29.03.2023